The Field of Business Sustainability and the Death Drive: A Radical Intervention - Bradshaw, Alan (Journal of business ethics, 2016)
We argue that the gap between an authentically ethical conviction of sustainability and a behaviour that avoids confronting the terrifying reality of its ethical point of reference is characteristic of the field of business sustainability. We do not accuse the field of business sustainability of ethical shortcomings on the account of this attitude–behaviour gap. If anything, we claim the opposite, namely that there resides an ethical sincerity in the convictions of business scholars to entrust capitalism and capitalists with the mammoth task of reversing, the terrifying reality of ecological devastation. Yet, the very illusory nature of this belief in capitalism’s captains to save us from the environmentally devastating effects of capitalism gives this ethical stance a tragic beauty. While sincere and authentic, it nevertheless is an ethical stance that relies on an “exclusionary gesture of refusing to see” (Žižek, in Violence, 2008, p. 52), what in psychoanalysis is referred to as a fetishist disavowal of reality. We submit that this disavowal is fetishistic because the act is not simply one of repressing the real. If it was, we would rightly expect that we could all see the truth if we only provide more or better information to fill the subject’s lack of knowledge. The problem is that the fetishist transfers a fantasy of the real as the real. In the case of destructive capitalism, the fetishist disavows that particular reality by believing in another, thus subjectively negating the lack (or gap). Therefore, from the perspective of psychoanalytic theory, we submit that the gap between attitude and behaviour is best understood not only as an ethical flaw, but also as an essential component of an ethics that makes possible the field of business sustainability.